RANCANGAN PERBAIKAN TATA LETAK MESIN PADA LANTAI PRODUKSI PRODUK CABLE NFA2XSY-T MENGGUNAKAN PAIRWISE EXCHANGE UNTUK MEMINIMASI WAKTU PRODUKSI DAN BIAYA MATERIAL HANDLING DI PT. SUCACO - Nenis Yuniarti; Sumiharni Batubara; Parwadi Moengin (JURNAL TEKNIK INDUSTRI, 2016)
PT. SUCACO Tbk is one of the biggest corporations that produces various types of cable thatis one of them cable medium / the high voltage. In the floor production medium / the high voltage therethere are problem that appeared after evaluated using the layout checklist and material handlingchecklist sheet at PT. SUCACO Tbk those are the rising of material handling costs and the productiontime. These problem caused by the layout the floor production strategy and also the use of materialhandling who has not yet been optimized. To solve the issues then the layout have to repaired by usingpairwise exchange method. So that will get the best layout in other word, the stranding machines willbe changed by cabling machines. By using the best layout proposal, promoted model will be simulatedthen. The results that gained by production time are decrease to 696 hour which is equal to 29 workingdays and for material handling costs which was originally have amount Rp. 482.268,53 decrease to Rp.414.662,93 after layout had been restoration. At the end after repair proposal was used, the issues thathappens at production floor medium/high voltage PT.SUCACO.Tbk. has been resolved. Furthermorethe addition of repairs proposal are used as company’s consideration and evaluation, which are thesecond proposal by adding 1 unit forklift material handling and replacing manual operator with trolley,the third proposal adding 2 unit drawing machines, 1 unit stranding machine and 2 unit extrudermachines in accordance with routing sheet calculation. The last proposal or the fourth, is combiningall of the proposal becoming the one.